Results of PCR diagnostics after gingiva soft tissue augmentation - A. B. Adzhieva; Z. S. Khabadze; H. M. Nalchajyan; S. S. Ivanov; E. A. Vasyuta (LLC "Endo Press", 2022)
Aim. To demonstrate the results of polymerase chain reaction in real time.Materials and methods. The gum fragment was placed in 1 ml of RNA-leiter ("QIAGEN", Germany), incubated for a day at +4C, samples were stored at -70 °C.To obtain cDNA from the RNA matrix, a ready-made set of reagents MMLV RT Kit ("Eurogen", Russia) was used, the reaction was carried out according to the attached instructions. 2 µl of random decanucleotide primer (Random dN) and 1 µl of sterile RNase-free water were added to 6 µl of RNA, heated at +70C in a "Termit" thermostat ("DNA-Technology", Russia) for 2 min to melt secondary RNA structures, then stored on ice (+4C). 4 ml of 5X buffer was added to the reaction mixture for the synthesis of the first chain (280 mM Tris-HCl, 375 mM KCl, 30 mM MgCl2, pH 8,7), 2 ml of dNTP mixture, 2 ml of DTT and 2 ml of sterile water free of RNase. Immediately before the reaction, 1 ml of MMLV revertase (reverse transcriptase of mouse leukemia virus) was added to the mixture and added to the RNA. The test tubes were heated in the Gnome thermostat ("DNA- Technology", Russia) at +39C for 60 minutes, then at +70C for 10 minutes in the "Termit" thermostat ("DNA-Technology", Russia).Results. The expression of IL-4, IL-10, IL-6, IL-12b, IL-1ß, MMP9 mRNA was not detected in the studied samples. The results of the polymerase chain reaction in real time showed that the expression levels of the proinflammatory cytokine TNFa and TIMP1 genes did not differ in both the autograft group and the collagen membrane group. The expression of MMP 2 and TIMP 2 was higher in the group using a collagen membrane, which is probably associated with tissue regeneration processes.Conclusions. Fibro-guide collagen matrix shows no less effective clinical results in comparison with autografts